2017
DOI: 10.1097/qai.0000000000001368
|View full text |Cite
|
Sign up to set email alerts
|

Viral Suppression and HIV Drug Resistance at 6 Months Among Women in Malawi's Option B+ Program: Results From the PURE Malawi Study

Abstract: Background In 2011, Malawi launched Option B+, a program of universal ART treatment for pregnant and lactating women to optimize maternal health and prevent pediatric HIV infection. For optimal outcomes, women need to achieve HIVRNA suppression. We report 6 month HIVRNA suppression and HIV drug resistance in the PURE study. Methods PURE study was a cluster-randomized controlled trial evaluating three strategies for promoting uptake and retention; Arm 1: Standard of Care, Arm 2: Facility Peer Support and Arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 13 publications
(13 reference statements)
7
32
1
Order By: Relevance
“…Our VL suppression estimate indicates that the Malawi PMTCT programme is close to reaching the final UNAIDS goal of 90% among HIV‐infected pregnant and breastfeeding women on ART. Similar estimates are documented in the postpartum period in three Option B+ study cohorts: 81.2% among Zimbabwean women at four to twelve weeks , 84% among Malawian women at six months postpartum and 84% among Rwandan women in late pregnancy/early postpartum . Among women who achieve VL suppression, the Malawi PMTCT programme shows remarkable reductions in MTCT.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our VL suppression estimate indicates that the Malawi PMTCT programme is close to reaching the final UNAIDS goal of 90% among HIV‐infected pregnant and breastfeeding women on ART. Similar estimates are documented in the postpartum period in three Option B+ study cohorts: 81.2% among Zimbabwean women at four to twelve weeks , 84% among Malawian women at six months postpartum and 84% among Rwandan women in late pregnancy/early postpartum . Among women who achieve VL suppression, the Malawi PMTCT programme shows remarkable reductions in MTCT.…”
Section: Discussionsupporting
confidence: 66%
“…We are limited by VL measures being obtained at four to twenty‐six weeks postpartum, without pre‐ART or pre‐delivery VL measures, and cannot comment on the trajectory of VL individually. Also, we cannot confirm incident infection among the 6.5% of women identified as new infections at screening/enrolment nor are we able to examine the potential role of drug resistance, as one study in Malawi reported a 35% resistance rate to NNRTIs among 55 HIV‐infected pregnant women . Finally, small numbers in the stratified VL categories may decrease MTCT accuracy and we did not account for site level clustering as the sample was derived from regional strata.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…In a cohort of newly diagnosed pregnant women, enrolled in the control arm of an intervention study before 28 weeks of gestation in some of the same clinics participating in the current study, 70% had undetectable viral load at six weeks postpartum although only 78% were on ART at enrolment . Similar levels of undetectable viral load were observed at delivery in a cohort of pregnant women initiated on ART at a median of 20 weeks of gestation in South Africa, and in Malawi . These data from cohort studies, combined with high levels of viral suppression in centrally located health zones suggest that with increased attention to the quality of care of the kind that is associated with cohort studies (avoidance of stockouts, better training and supervision of providers among others), higher rates of viral suppression can be achieved among pregnant and breastfeeding women in care, no matter the settings.…”
Section: Discussionsupporting
confidence: 61%
“…Additional efforts to help mothers continue their outpatient HIV care and viral suppression beyond the perinatal period are needed. Engagement in care among our participants (89% and 90% at 6 and 12 months, respectively) was higher than published estimates from other studies of women enrolled in Option B+ in Malawi, which ranged from 75% to 83% over 6–12 months after ART initiation , even using the same Malawi Ministry of Health definition of lost to follow‐up (>60 days since attending a scheduled clinic visit for ART) . The current study's participants may have been more motivated to return for their clinic visits and adhere to their ART regimen because they received a transport stipend provided as part of study participation, had positive view of care received from study staff, because the study clinic was less crowded than the government clinic, or because they desired to be part of a research program.…”
Section: Discussioncontrasting
confidence: 77%